Accelerated discovery and mechanical property characterization of bioresorbable amorphous alloys in the Mg–Zn–Ca and the Fe–Mg–Zn systems using high-throughput methods. Issue 35 (14th August 2019) - Datye, Amit; Alexander Kube, Sebastian; Verma, Devendra; Schroers, Jan; Schwarz, Udo D.
Abstract : High throughput discovery of amorphous bioresorbable alloys. Top: combinatorial sputtering setup. Bottom: composition of libraries deposited on silicon (Si) wafers for (a) magnesium (Mg)–zinc (Zn)–calcium (Ca) and the (b) iron (Fe)–Mg–Zn systems. Abstract : Ternary amorphous alloys in the magnesium (Mg)–zinc (Zn)–calcium (Ca) and the iron (Fe)–Mg–Zn systems are promising candidates for use in bioresorbable implants and devices. The optimal alloy compositions for biomedical applications should be chosen from a large variety of available alloys with best combination of mechanical properties (modulus, strength, hardness) and biological response ( in situ degradation rates, cell adhesion and proliferation). As a first step towards establishing a database designed to enable such targeted material selection, amorphous alloy composition libraries were fabricated employing a combinatorial magnetron sputtering approach where Mg, Zn, and Ca/Fe are co-deposited from separate sources onto a silicon wafer substrate. Composition analysis using energy dispersive X-ray spectroscopy documented a composition range of ∼15–85 at% Mg, ∼6–55 at% Zn, and ∼5–60 at% Ca for the Mg–Zn–Ca library and ∼26–84 at% Mg, ∼10–61 at% Zn, and ∼7–55 at% Fe for the Fe–Mg–Zn library. X-ray diffraction measurements established that amorphous alloys ( i.e., glasses) form in almost the entire range of composition at the high cooling rates during sputtering for both alloy libraries. Finally, the effective material modulus, the Oliver–Pharr hardness, and the yield strength values obtained using nanoindentation reveal a wide range of mechanical properties within both systems.